Genomic Diversity of Azole-Resistant Aspergillus fumigatus in the United States - Kizee A. Etienne (American Society for Microbiology, 2021)
ABSTRACT Azole resistance in pathogenic Aspergillus fumigatus has become a global public health issue threatening the use of medical azoles. The environmentally occurring resistance mutations, TR34/L98H (TR34) and TR46/Y121F/T289A (TR46), are widespread across multiple continents and emerging in the United States. We used whole-genome single nucleotide polymorphism (SNP) analysis on 179 nationally represented clinical and environmental A. fumigatus genomes from the United States along with 18 non-U.S. genomes to evaluate the genetic diversity and foundation of the emergence of azole resistance in the United States. We demonstrated the presence of clades of A. fumigatus isolates: clade A (17%) comprised a global collection of clinical and environmental azole-resistant strains, including all strains with the TR34/L98H allele from India, The Netherlands, the United Kingdom, and the United States, and clade B (83%) consisted of isolates without this marker mainly from the United States. The TR34/L98H polymorphism was shared among azole-resistant A. fumigatus strains from India, The Netherlands, the United Kingdom, and the United States, suggesting the common origin of this resistance mechanism. Six percent of azole-resistant A. fumigatus isolates from the United States with the TR34 resistance marker had a mixture of clade A and clade B alleles, suggestive of recombination. Additionally, the presence of equal proportions of both mating types further suggests the ongoing presence of recombination. This study demonstrates the genetic background for the emergence of azole resistance in the United States, supporting a single introduction and subsequent propagation, possibly through recombination of environmentally driven resistance mutations. IMPORTANCE Aspergillus fumigatus is one of the most common causes of invasive mold infections in patients with immune deficiencies and has also been reported in patients with severe influenza and severe acute respiratory syndrome coronavirus 2 (SARs-CoV-2). Triazole drugs are the first line of therapy for this infection; however, their efficacy has been compromised by the emergence of azole resistance in A. fumigatus, which was proposed to be selected for by exposure to azole fungicides in the environment [P. E. Verweij, E. Snelders, G. H. J. Kema, E. Mellado, et al., Lancet Infect Dis 9:789–795, 2009, https://doi.org/10.1016/S1473-3099(09)70265-8]. Isolates with environmentally driven resistance mutations, TR34/L98H (TR34) and TR46/Y121F/T289A (TR46), have been reported worldwide. Here, we used genomic analysis of a large sample of resistant and susceptible A. fumigatus isolates to demonstrate a single introduction of TR34 in the United States and suggest its ability to spread into the susceptible population is through recombination between resistant and susceptible isolates.